Teacher’s experiences in character education for autistic children - Hanif Cahyo Adi Kistoro; Caly Setiawan; Eva Latipah; Himawan Putranta (Institute of Advanced Engineering and Science, 2021)
Character education is also important given to autistic children. This phenomenological research aims to reveal the teacher's experience in teaching character education for autistic children. The participants in this research were 10 teachers from three exceptional schools consisting of public and private exceptional schools. In-depth interview method as a data collection technique. Data analysis using semantic reduction is carried out by the stages of identifying important statements from the results of the interview, determining the theme of the discussion, and describing the significance of the whole the teacher's experience. The results found that character learning for autistic children through three models, namely explanatory, practice, and intensive mentoring. The explanatory model is used to practice the ability of autistic children in terms of building children's concentration and focus. The practice model is used to train autistic children soft skills in terms of strengthening the understanding of the material and its reasoning ability. While the intensive mentoring model for training soft skills autistic children related to the ability of interpersonal relationships and confidence. Therefore, the inclusion of teacher competencies must at a minimum include pedagogical, personal, and social abilities to teach character education for autistic children.